Composition of natural phytoplankton community has minor effects on autochthonous dissolved organic matter characteristics. Issue 4 (3rd July 2019) - Haraguchi, Lumi; Asmala, Eero; Jakobsen, Hans H.; Carstensen, Jacob
ABSTRACT: Dissolved organic matter (DOM) is an important component of nutrient cycling, but the role of different organisms controlling the processing of autochthonous DOM remains poorly understood. Aiming to characterize phytoplankton-derived DOM and the effects of complex pelagic communities on its dynamics, we incubated natural plankton communities from a temperate mesohaline estuary under controlled conditions for 18 days. The incubations were carried out in contrasting seasons (spring and autumn) and changes in the planktonic community (phytoplankton, bacteria and microzooplankton), nutrients and DOM were assessed. Our results highlight the complexity of DOM production and fate in natural planktonic communities. Small changes in DOM composition were observed in the experiments relative to the orders-of-magnitude variations experienced in the phytoplankton assembly. We argue that the tight coupling between microbial processing and DOM production by phytoplankton and grazers stabilizes variations in quantity and characteristics of autochthonous DOM, resulting in apparently homogeneous semi-labile DOM pool throughout the experiments. However, seasonal differences in the production and processing of DOM were observed, reflecting differences in the nutrient regimes and initial DOM characteristics in each experiment, but also likely influenced by changes in the successional status of the pelagic community. Acknowledging that characteristics of the DOM derived from phytoplankton growth can vary broadly, heterotrophic processing and successional status of the community are synergistically important factors for shaping those characteristics, and thus affecting the seasonal signature of the semi-labile autochthonous DOM pool.